Seed exudates of Sesbania virgata (Cav.) Pers. stimulate the asymbiotic phase of the arbuscular mycorrhizal fungus Gigaspora albida Becker & Hall - Coelho, Leilyane C.S.; Mignoni, Daiane S.B.; Silva, Fábio S.B.; Braga, Márcia R. (Hoehnea, 2019)
ABSTRACT Sesbania virgata is a legume used in the restoration of degraded areas and forms a symbiosis with arbuscular mycorrhizal fungi (AMF). Its seeds exude secondary metabolites that may influence the colonization by AMF. In this work, we studied the effects of seed (SE) and root exudates (RE) of S. virgata on the asymbiotic phase of Gigaspora albida. Spores of G. albida were germinated in medium supplemented with different concentrations of SE or RE. After seven days, spore germination was stimulated (46.6%) in the medium supplemented with the highest concentration of SE, while the mycelial growth was stimulated with the lowest SE concentration. In turn, RE had no effect on the fungal asymbiotic phase. We concluded that SE exert a positive effect on the asymbiotic phase of G. albida and that the different effects between SE and RE of S. virgata can be explained by their distinct content of secondary metabolites. RESUMO Sesbania virgata é uma leguminosa utilizada na restauração de áreas degradadas e que forma simbiose com fungos micorrízicos arbusculares (AMF). Suas sementes exudam metabólitos secundários que podem influenciar a colonização pelos AMF. Neste trabalho, estudamos os efeitos de exsudatos de sementes (SE) e radiculares (RE) de S. virgata na fase assimbiótica de Gigaspora albida. Esporos de G. albida foram germinados em meio suplementado com diferentes concentrações de SE ou RE. Após sete dias, a germinação dos esporos foi estimulada (46,6%) com a maior concentração de SE, enquanto o crescimento micelial foi estimulado com a menor concentração de SE. Por sua vez, RE não teve efeito na fase assimbiótica de G. albida. Conluiu-se que SE exercem efeitos positivos na fase assimbiótica de G. albida e que os efeitos diferenciais entre SE e RE de S. virgata na fase de assimbiótica fúngica podem ser explicados pelo seu conteúdo distinto de metabólitos secundários.